PENGARUH MODEL TREFFINGER TERHADAP HASIL BELAJAR KOGNITIF SISWA PADA MATERI SISTEM PERTIDAKSAMAAN LINEAR DUA VARIABEL - Jannah, Miftakhul; Sukarma, I Ketut; Nissa, Ita Chairun (Media Pendidikan Matematika, 2019)
Students’ knowledge about apperception material is important in supporting the success of a learning. One of the learning innovations to maximize apperception material can be done with treffinger learning model. This research aims to find out how the effect of the learning model treffinger on students’ cognitive learning outcomes for the subject of two variables linear inequality system. This research was conducted at SMA Negeri 1 Gunungsari, West Lombok. The research design used is quasi experimental design. Sampling in this study uses simple random sampling technique. X MIA 3 class as an experimental class and X MIA 1 class as a control class. The research instrument was a test sheet and observation sheet for the implementation of the learning model treffinger. The results of the research were obtained by using t-test, the average score of cognitive results of the experimental class students was 68.88 and the control class was 64.10, obtained tcount>ttable (2.557 > 2.042). So it can be conclude that H0 is rejected and Ha is accepted, this means that there are significant treffinger learning model towards students cognitive learning outcomes in materials twi variable linear inequality system at class X grade of SMA Negeri 1 Gunungsari academic year 2018/2019.